Use of antibiotic-loaded bone cement for paediatric chronic osteomyelitis: a scoping review - Muhammad Talal Ibrahim; Muhammed Wahhaab Sadiq; Farah Naz Qamar; Shahryar Noordin (Journal of the Pakistan Medical Association, 2026)
Objective: To systematically map the research done on the use of antibiotic-loaded bone cement for paediatric chronic osteomyelitis. Method: The scoping review was conducted in July 2023, and comprised research on PubMed, Scopus, Cochrane, Google Scholar and ScienceDirect databases for original research articles on paediatric chronic osteomyelitis using antibiotic-loaded bone cement. Data items extracted included basic bibliographic details, patient demographics, patient presentation, pathogen, systemic and local antibiotic treatment, operative techniques, follow-up, outcomes, and complications. Results: Of the 1,569 studies identified, 158(10.07%) were assessed for eligibility, and, of them, 9(5.7%) were reviewed in detail. All the 9(100%) studies were retrospective, 6(66.6%) were case series, and 1(11.1%) was from a developing country. Of the total 73 patients in the studies, 58(79.5%) were males, and tibia was the most commonly involved bone 21(46%). Vancomycin was most commonly used in bone cement (60 (83.6%)). All 73 (100%) patients were infection-free at the end of the follow-up period, with no major complications in 55 (75.3%) patients. Conclusion: Current literature on the use of antibiotic-loaded bone cement in paediatric chronic osteomyelitis is limited, but favours its use. Key Words: Paediatric, Chronic osteomyelitis, Antibiotic, Bone cement, Bone infection